UJI ORGANOLEPTIK PADI GALUGU DAN PADI KARUNG DI KENAGARIAN PULASAN KECAMATAN TANJUNG GADANG KABUPATEN SIJUNJUNG - Syaifuddin Islami; Marpinas Marpinas (Ensiklopedia of Journal, 2023)
Rice is the staple food of Indonesian people. The lampai kuniang rice is a local variety of rice from Nagari Aie Angek, Sijunjung District which has become a national variety rice seed. In an effort to extend the shelf life of rice, one of the efforts can be done by storing rice as food reserves. Nagari Palasan one of Tanjung Gadang District, Sijunjung Regency has its own uniqueness in storing rice grain and people call it Galugu. The existence of the rice barn (Galugu) is a historical relic which is part of the cultural heritage in Palasan village. The Galugu form consists of boundaries or partitions using boards with grain on the floor (rumah gadang). Galugu has multiple functions, apart from storing grain, it can also be used as a seat for the ninik mamak of a tribe at traditional events. The method used in this research is an observation method or survey, which is analyzed descriptively by analyzing rice from storage of galugu rice and sack rice and by liking or subjectively testing with the parameters Slightly Dislike, Dislike, Neutral, Somewhat Like, Like and Very Like. The results obtained in the storage of galugu rice and sack rice were dominant in the storage of galugu rice on the color indicator 5.00 and taste 4.89Keywords: galugu, lumbung, rice